2024
DOI: 10.1111/jcmm.18257
|View full text |Cite
|
Sign up to set email alerts
|

Huayu Qutan Recipe promotes lipophagy and cholesterol efflux through the mTORC1/TFEB/ABCA1‐SCARB1 signal axis

Yue Li,
Jiaxiang Pan,
J. J. Jiajia Yu
et al.

Abstract: This study aims to investigate the mechanism of the anti‐atherosclerosis effect of Huayu Qutan Recipe (HYQT) on the inhibition of foam cell formation. In vivo, the mice were randomly divided into three groups: CTRL group, MOD group and HYQT group. The HYQT group received HYQT oral administration twice a day (20.54 g/kg/d), and the plaque formation in ApoE−/− mice was observed using haematoxylin–eosin (HE) staining and oil red O (ORO) staining. The co‐localization of aortic macrophages and lipid droplets (LDs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Recent research indicates that mTOR inhibition can decrease the cardiovascular risk through various mechanisms. For instance, Huayu Qutan Recipe (HYQT ), a compound of traditional Chinese herbal medicine, exhibits anti-atherosclerosis effects by inhibiting foam cell formation through the promotion of lipophagy and cholesterol efflux via the mTORC1/TFEB/ABCA1-SCARB1 signal axis [ 41 ]. Li et al investigated how both Huayu Qutan Recipe and rapamycin (both mTOR inhibitors) enhance cholesterol efflux.…”
Section: Key Evidence Of the Pivotal Role Of Mtor Non-skin Manifestat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research indicates that mTOR inhibition can decrease the cardiovascular risk through various mechanisms. For instance, Huayu Qutan Recipe (HYQT ), a compound of traditional Chinese herbal medicine, exhibits anti-atherosclerosis effects by inhibiting foam cell formation through the promotion of lipophagy and cholesterol efflux via the mTORC1/TFEB/ABCA1-SCARB1 signal axis [ 41 ]. Li et al investigated how both Huayu Qutan Recipe and rapamycin (both mTOR inhibitors) enhance cholesterol efflux.…”
Section: Key Evidence Of the Pivotal Role Of Mtor Non-skin Manifestat...mentioning
confidence: 99%
“…At the same time, HY1485 (an mTOR agonist) counteracts the effects of Huayu Qutan Recipe by reducing cholesterol efflux. This study concluded that HYQT may lower the cardiovascular risk by boosting cholesterol efflux and degrading macrophage-derived foam cell formation through the mTOR/TFEB signaling pathway [ 41 ].…”
Section: Key Evidence Of the Pivotal Role Of Mtor Non-skin Manifestat...mentioning
confidence: 99%